PENGARUH PERSEPSI WAJIB PAJAK TENTANG KEBIJAKAN TAX AMNESTY (PENGAMPUNAN PAJAK), DAN MOTIVASI MEMBAYAR PAJAK TERHADAP KEPATUHAN PERPAJAKAN - Suyanto Suyanto; Ika Septiani Putri (Jurnal Akuntansi, 2017)
ABSTRACT: This research aim to know the influence of Perception taxpayers on tax amnesty and motivation to pay taxes toward Taxpayer Compliance at Regional Office Directorate General of Taxation Wonosari, Gunungkidul. The sample collection technique used in this research was convenience sampling, data analysis techniques used in this research were multiple linear regression. This research result indicated: Perception taxpayers on tax amnesty not had influence positive and significant toward Taxpayer Compliance it is proven by the value of tamount < ttable (1,386 < 1,9901) and significantly 0,170 > 0,05,, Motivation to Pay Taxes influence has positive and significant toward Taxpayer Compliance it is proven by the value of tamount > ttable (2,125 > 1,9901) and significantly 0,037 < 0,05, Perception taxpayers on tax amnesty and Motivation to Pay Taxes has positive and significant toward Taxpayer Compliance it is proven by the value of Famount > Ftable (4,829 > 3,11) and significantly 0,010 < 0,05.. Key Words : Perception taxpayers on tax amnesty, Motivation to Pay Taxes, and Taxpayer Compliance